ETYMOLOGICAL ANALYSIS OF THE TERM OF ART - Zokirjonov , Abbosbek Zokirjon o‘g‘li (Educational Research in Universal Sciences, 2023)
The article examines the linguistic and cultural analysis of the concept of "art" and the etymology of this word. It is devoted to the importance of art in the development of culture.